WHY STUDY ERROR? - Irawansyah Irawansyah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT There are many students still doing errors or mistakes in learning English as a foreign language (EFL) in Indonesia. Therefore, it is very important to study error. The error itself has long been an interest among foreign language researchers. The main task of error is how to describe a learning which occurs by examining students' output. It consists of correct and incorrect utterances. In this case, there are two approaches to learning students' errors, namely error analysis (EA) and contrastive analysis (CA). This paper only explains how error analysis is important in the teaching-learning process. It has many advantages when it is learned. EA has been classified into four types: linguistics category taxonomy, surface strategy taxonomy, comparative taxonomy, and communicative effect taxonomy. This study found error as an important tool for teachers and students to observe students’ learning process and learning strategies. ABSTRAK Ada masih banyak siswa yang melakukan error atau mistake dalam pembelajaran bahasa Inggris sebagai bahasa asing (EFL) di Indonesia. Oleh karena itu, hal ini sangat penting untuk mempelajari error. Error itu sendiri sudah lama menjadi perhatian peneliti-peneliti bahasa asing. Fungsi utama dari error itu sendiri adalah bagaimana mendeskripsikan pembelajaran yang terjadi dengan memeriksa hasil siswa. Hal ini terdiri dari ujaran yang benar dan salah. Dalam hal ini, ada dua pendekatan dalam mempelajari kesalahan siswa, yaitu analisis error (EA) dan analisis kontrastif (CA). Makalah ini hanya untuk menjelaskan bagaimana error analisis yang mempunyai banyak pengaruh dalam proses pembelajaran. Error analysis telah dikelompokkan menjadi empat jenis, yaitu kategori linguistik, kategori permukaan, kategori komparatif, dan kategori komunikatif. Temuan penelitian ini menyampaikan bahwa error sebagai sebuah alat yang penting bagi guru dan siswa untuk mengamati proses belajar dan strategi pembelajaran siswa. How to Cite: Irawansyah (2017). Why Study Error?. IJEE (Indonesian Journal of English Education), 4(2), 120-129. doi:10.15408/ijee.v4i2.5972